Law Enforcement Regarding The Involvement of Indonesian Citizens Affiliated with Global Terrorism Organizations - Pakpahan, David Roger Julius; Wahyudi, Slamet Tri; Prasetyo, Handoyo (MSJ : Majority Science Journal, 2024)
Indonesia has become one of the top priorities for global terrorist groups. The criminal act of terrorism that occurred in Indonesia is a severe crime and endangers state ideology, state security, state sovereignty, human values ​​, and various aspects of social life. To improve law enforcement against the involvement of Indonesian citizens in global terrorist organizations, cooperation between multiple institutions and related stakeholders is very important. This research aims to determine the obstacles law enforcement faces regarding global terrorist organizations. This research uses normative research methods and primary, secondary, and tertiary legal material sources. Law enforcement related to global terrorist organizations faces several complex obstacles. The complexity of terrorist networks makes it challenging to identify members and collect sufficient evidence. The use of digital technology and covert communications by terrorist organizations makes monitoring and gathering evidence difficult. Jurisdictional limitations and barriers to international cooperation hinder the exchange of information and the extradition of terrorist perpetrators. To overcome these obstacles, inter-agency cooperation, increased technical capacity, effective exchange of information, and strong international cooperation are key factors in law enforcement efforts against global terrorist organizations.